Imaging diagnostics for transitional discs - Ovelar, M. de Juan; Min, M.; Dominik, C.; Thalmann, C.; Pinilla, Paola; Benisty, M.; Birnstiel, T. (Astronomy and astrophysics, 2013)
Transitional discs are a special type of protoplanetary disc, where planet formation is thought to be taking place. These objects feature characteristic inner cavities and/or gaps of a few tens of AUs in sub-millimetre images of the disc. This signature suggests a localised depletion of matter in the disc that could be caused by planet formation processes. However, recent observations have revealed differences in the structures imaged at different wavelengths in some of these discs. In this paper, we aim to explain these observational differences using self-consistent physical 2D hydrodynamical and dust evolution models of these objects, assuming their morphology is indeed generated by the presence of a planet. We use these models to derive the distribution of gas and dust in a theoretical planet-hosting disc for various planet masses and orbital separations. We then simulate observations of the emitted and scattered light from these models with Very Large Telescope (VLT)/SPHERE-ZIMPOL, Subaru/HiCIAO, VLT/VISIR, and ALMA. We do this by first computing the full resolution images of the models at different wavelengths and then simulating the observations while accounting for the characteristics of each particular instrument. The presence of the planet generates pressure bumps in the gas distribution of the disc, whose characteristics strongly depend on the planet mass and position. These bumps cause large grains to accumulate, while small grains are allowed into inner regions. This spatial differentiation of the grain sizes explains the differences in the observations, since different wavelengths and observing techniques trace different parts of the dust size distribution. Based on this effect, we conclude that the combination of visible/near-infrared polarimetric and sub-mm images is the best strategy to constrain the properties of the unseen planet responsible for the disc structure.
Gesehen am 09.12.2021